2013
DOI: 10.1371/journal.pone.0080345
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Potential of Plasmatic MicroRNA Signatures in Stable and Unstable Angina

Abstract: PurposeWe examined circulating miRNA expression profiles in plasma of patients with coronary artery disease (CAD) vs. matched controls, with the aim of identifying novel discriminating biomarkers of Stable (SA) and Unstable (UA) angina.MethodsAn exploratory analysis of plasmatic expression profile of 367 miRNAs was conducted in a group of SA and UA patients and control donors, using TaqMan microRNA Arrays. Screening confirmation and expression analysis were performed by qRT-PCR: all miRNAs found dysregulated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
93
3
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(103 citation statements)
references
References 31 publications
6
93
3
1
Order By: Relevance
“…Similar results were reported when a set of microparticle-derived pro-inflammatory miRNAs from plasma of 10 patients was observed to discriminate between SAP and UAP [90]. Although a similar approach could not validate these results [26], promising results were reported in a clinical screening-validation setting comprising 46 UAP patients compared with 63 NCCP patients [37]. The authors found a miRNA signature consisting of miR-132, miR-150, and miR-186, which strongly discriminated UAP and NCCP [37].…”
Section: Mirnas In the Diagnosis Of Unstable And Stable Angina Pectorsupporting
confidence: 60%
“…Similar results were reported when a set of microparticle-derived pro-inflammatory miRNAs from plasma of 10 patients was observed to discriminate between SAP and UAP [90]. Although a similar approach could not validate these results [26], promising results were reported in a clinical screening-validation setting comprising 46 UAP patients compared with 63 NCCP patients [37]. The authors found a miRNA signature consisting of miR-132, miR-150, and miR-186, which strongly discriminated UAP and NCCP [37].…”
Section: Mirnas In the Diagnosis Of Unstable And Stable Angina Pectorsupporting
confidence: 60%
“…So far more than 2000 human miRs have been identified and some have been associated with the development of disease including cardiovascular disease. Although investigators have reported that specific plasmatic miR signatures appear to be associated with stable or unstable IHD, the ability to distinguish between stable and unstable disease seems limited (62 ). Moreover, limited data have been available concerning the prognostic value in stable IHD (63 ), but a recent report suggests that miR-132, miR-140 -3p, and miR-210 may predict death in patients with ACS (64 ).…”
Section: Novel Biomarkersmentioning
confidence: 99%
“…1) Among these patients, 50% are due to acute coronary syndrome (ACS), including stable angina (SA), unstable angina (UA), and myocardial infarction. 2) Myocardial infarction can be diagnosed by the elevated plasmatic levels of cardiac-specific protein troponin. However, there are no established circulating biomarkers that may distinguish SA and UA currently, and the latter, as a kind of ACS, is more likely to develop into myocardial infarction and result in an increase in mortality.…”
mentioning
confidence: 99%